Design and PIC Simulation of Millimeter Wave Stagger Tuned Gyro-twystron - Veerababu V.; Yadav S.G.; Thottappan M.; Dwivedi S. (My University, 2025)
In this article, the design of a staggered-tuned millimeter wave gyro-twystron amplifier and its PIC simulation are presented. The stagger tuning method increases the amplifier's bandwidth, which is beneficial for radar applications. The entire amplifier RF structure has been modeled in the 'CST Particle Studio' to analyze an interaction between electron beam and wave. The present simulation predicted 340 kW RF power with 48% efficiency, 61 dB gain, and 2.8 GHz bandwidth for the beam characteristics of 70 kV, 10 A. © 2022 IEEE.